Prevalence of key potentially inappropriate drugs use in pediatrics: a cross-sectional study - Mariam Jihad Diab; Sham ZainAlAbdin; Salah Aburuz; Rami Beiram; Amal Akour; Anan Jarab; Tasnim Dawoud (BMC, 2024)
Abstract Background Appropriate drug prescribing in the pediatric population is challenging, given this age group's unique pharmacokinetics. This has inevitably led to a high incidence of adverse drug reactions in this population. To address this issue, the Pediatric Pharmacy Association (PPA) compiled a list of 67 drugs that are inappropriately used in the pediatric population called the Key Potentially Inappropriate Drugs "KIDs list". Aim To estimate the prevalence of potentially inappropriate medications (PIM) use in pediatric wards based on the KIDs list criteria. Methods A retrospective observational study was conducted and included pediatric patients who were admitted to five pediatric wards during 3 years (2019-2021). The drugs in the KIDs list were matched to the hospital formulary and 11 matched drugs were included in the study. For each individual drug, the patient's electronic file was reviewed to determine the prescription appropriateness according to the KIDs list criteria. Results Among 3,166 pediatric patients admitted to pediatric wards, a total of 415 patients received a PIM listed in the KIDs list. The mean age was 8.6 (± 4.9) years old, and 60.0% (n = 251/415) were males. The overall prevalence of PIM use was 13.0% (n = 415/3166). Among the prescribed PIM, metoclopramide was the most commonly prescribed PIM 42.8% (n = 178/415), followed by tramadol 37.6% (n = 156/415). Conclusion Given the high prevalence of inappropriate medication use in the pediatric wards, future research on strategies and interventions should be recommended to limit the use of PIMs and provide safer alternatives for the pediatric population.